Efficacy of Intravitreal Bevacizumab versus Combination of Intravitreal Triamcinolone Acetonide and Bevacizumab in the Treatment of Centre Involving Diabetic Macular Edema (Journal of National Institute of Ophthalmology, 2026)
Purpose: To compare the efficacy of intravitreal bevacizumab (IVB) and the combination of IVB and intravitreal triamcinolone (IVT) in the treatment of centre involving DME patients. Methodology: This prospective observational study was conducted on 60 eyes of 60 patients of diabetic macular oedema attending in department of Vitreo-retina, they were selected purposively based on specific criteria. All patients underwent general preoperative routine examinations, electrocardiogram and blood tests that included glycosylated hemoglobin (HbA1c). All selected patient underwent detailed ocular and systemic examination as well as relevant investigations with special attention to assessment visual acuity and measurement of central macular thickness by OCT. Selected patients were grouped into group-A and group-B. They were randomly assigned with intra-vitreal injection of bevacizumab (1.25mg/0.05ml) in group-A and combination of intra-vitreal bevacizumab (1.25mg/0.05ml)and triamcinolone (1mg/0.05ml) in group-B. Injections were given monthly for 3 months in every patients. They were followed-up after 1 month and 3 months of injection. Best-corrected visual acuity (BCVA) in log MAR unit, central macular thickness (CMT) in μm by OCT, IOP by Goldman applanation tomnometry  were done in every follow-up. Mean value of BCVA, CMT, cataract grading and IOP during follow-up periods were compared with that of baseline value to assess the significance of changes within the group as well as with other group to assess the significance of changes between the groups. Statistical analysis were done by using window software SPSS ver. 21. Chi-square test, paired and un-paired ’t’ test were done in applicable cases. p